PERISTILAHAN DALAM ADAT MEMAPAK DURIAN PADA MASYARAKAT MELAYU KABUPATEN KETAPANG - Dwitamaya, Sella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to describe the local languages, especially dialect of Melayu Ketapang in the tradition of Memapak Durian at Ketapang district. This research belongs to qualitative. This research conducted in Sembelangaan,Nanga Tayap, Ketapang. The problems of this study are includes the inventory of terminology in the tradition of Memapak Durian, the components of meaning, cultural meanings, and semantic functions. The purpose of this study is to describe the terminology of the tradition of Memapak Durian in the Melayu ethnic at Ketapang city. The data of this study is taken from the informant in that area and the procession of Memapak Kembang Durian, Memapak Durian Jatuh, Mengantar Buah Durian. This research used direct observation method. The techniques of collecting data in this study are interviewing, recording, making note and taking a picture techniques. Based on the results of the data aabove the researcher found 41 leksem. Analysis of the component of meaning in the procession of Memapak Kembang Durian found 34 leksem. The researcher found 16 laksem from the procession of Memapak Durian Jatuh and 10 laksem from the procession of mengantar buah durian. In the description of semantic function from the tradition of memapak durian, the researcher was found 41 laksem.Â Keywords: Terminology, Terminology In Tradition, Semantic, Malay Of Â Â Ketapang